Nondestructive testing of native and tissue-engineered medical products: adding numbers to pictures. Issue 2 (February 2022) - Castro, Nathan J.; Babakhanova, Greta; Hu, Jerry; Athanasiou, K.A.
Abstract : Traditional destructive tests are used for quality assurance and control within manufacturing workflows. Their applicability to biomanufacturing is limited due to inherent constraints of the biomanufacturing process. To address this, photo- and acoustic-based nondestructive testing has risen in prominence to interrogate not only structure and function, but also to integrate quantitative measurements of biochemical composition to cross-correlate structural, compositional, and functional variances. We survey relevant literature related to single-mode and multimodal nondestructive testing of soft tissues, which adds numbers (quantitative measurements) to pictures (qualitative data). Native and tissue-engineered articular cartilage is highlighted because active biomanufacturing processes are being developed. Included are recent efforts and prominent trends focused on technologies for clinical and in-process biomanufacturing applications. Highlights: Optics-based nondestructive techniques have shown to produce corroborative and congruent results to traditional tests. Rapid, label-free, and quantitative spectroscopy can elucidate critical quality attributes when coupled to optical imaging and elastography for functional TEMPs. Multimodal nondestructive tools can be facilitated by miniaturizing the form factor of probes leading to holistic assessment of tissues and TEMPs. Fiber-coupled tools may be more amenable to coupling with other technologies as well as deployable aseptically for in-process and automated assessment of TEMPs while providing real-time feedback and quality control/assurance in scalable bioprocesses. There is an outstanding need for standards development that will enable the translation, increase safety and reliability, improve in-process efficiency, and decrease the overall costs of TEMPs biomanufacturing.